Analisis Hukum Penetapan Tarif PNBP Pada Pihak Tertentu Dalam Percepatan Sertifikasi Tanah - Safrin Salam (Justitia Jurnal Hukum, 2017)
Land is a place for human life and in the present context has become a primary need forthe Indonesian people. The presence of Land Registry and its cheap and affordableprinciples contained therein is one model of land reform, implemented by the government. This study aimed to analyze the procedure of granting tariff reception State Tax On certain Parties in speeding up the certificate of ownership of land and analyze ideally decide granting tariff setting state revenue tax on certain parties to be implemented according to the principles of land registration. This study uses normative legal research using secondary data in the form of primary legal materials and secondary materials. The results showed that the procedure of tariff setting state revenue Taxes On Certain Parties in speeding up the certificate of land ownership can be reached by Perma ATR / BPN No. 25 2015 effectively and efficiently that the applicant apply for tariff setting state revenue instead of taxes and then meet the requirements specified Perma ATR / BPN No. 25 Years 2015.sedangkan decide granting tariff setting state revenue tax on certain parties to be implemented according to the principles of land registration is with the issuance of a decree regulating the finance minister of land registration fee for a particular party are the responsibility of the State or are exempt from levy fees by the State , Suggestions from this study is the Ministry of Finance should immediately issue the finance minister about the costs that regulated Perma ATR / BPN No. 25, 2015 has been charged by the State then other ministries need to commit firmly on running a land reform program that has been mandated by Law No. 5 of 1960 on the Basic Regulation of Agrarian as a way to equalize land ownership in Indonesia by the whole society. Keywords: PNBP, Specific Parties, Certified Land